Notch Regulates Macrophage-Mediated Inflammation in Diabetic Wound Healing - Kimball, Andrew S.; Joshi, Amrita D.; Boniakowski, Anna E.; Schaller, Matthew; Chung, Jooho; Allen, Ronald; Bermick, Jennifer; Carson, William F.; Henke, Peter K.; Maillard, Ivan; Kunkel, Steve L.; Gallagher, Katherine A. (Frontiers in Immunology, 2017)
Macrophages are essential immune cells necessary for regulated inflammation during wound healing. Recent studies have identified that notch plays a role in macrophage-mediated inflammation. Thus, we investigated the role of notch signaling on wound macrophage phenotype and function during normal and diabetic wound healing. We found that notch receptor and ligand expression are dynamic in wound macrophages during normal healing. Mice with a myeloid-specific notch signaling defect (DNMAMLfloxedLyz2Cre+), demonstrated delayed early healing (days 1-3) and wound macrophages had decreased inflammatory gene expression. In our physiologic murine model of type 2 diabetes (T2D), Notch receptor expression was significantly increased in wound macrophages on day 6, following the initial inflammatory phase of wound healing, corresponding to increased inflammatory cytokine expression. This increase in Notch1 and Notch2 was also observed in human monocytes from patients with type 2 diabetes (T2D). Further, in pre-diabetic mice with a genetic notch signaling defect (DNMAMLfloxedLyz2Cre+ on a high fat diet), improved wound healing was seen at late time points (days 6-7). These findings suggest that notch is critical for the early inflammatory phase of wound healing and directs production of macrophage-dependent inflammatory mediators. These results identify that canonical notch signaling is important in directing macrophage function in wound repair and define a translational target for the treatment of non-healing diabetic wounds.